Gestational trophoblastic disease in the delayed postpartum period - De La Vega, Guillermo Antonio (2021)
Gestational trophoblastic disease (GTD) is a term used for a group of pregnancyrelated tumors arising from defective proliferation of trophoblastic tissue. Its incidence after term pregnancy is infrequent, being diagnosed in most cases incidentally, due to symptoms of metastasis. We present a case of GTD that occurred 9 weeks after a vaginal delivery at term. The serum beta-human chorionic gonadotropin (β-hCG) level was 38 084 mIU/mL and a chest CT scan showed multiple pulmonary nodules. The patient received actinomycin D for 3 cycles. The β-hCG normalized after the third cycle and the patient remained disease-free for 12 months after diagnosis. The clinical presentation and challenges in diagnosing GTD in the late postpartum period are described.